Developing a Social Constructivist Group Counseling Model to Support the Development of Senior High School Students’ Speaking Skills - Siska Kuamala Hatrianti; Abdul Rozak; Jimat Susilo (JOLLT Journal of Languages and Language Teaching, 2026)
Speaking skills are essential competencies that enable students to express ideas, opinions, and experiences clearly in academic and social contexts. However, many senior high school students still experience difficulties in organizing thoughts, speaking confidently, and participating actively in oral communication. This study aimed to develop a group counseling model based on a social constructivist approach to support students’ speaking skills. The research employed a Research and Development design using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. In the needs analysis stage, participants included 79 students, three guidance and counseling teachers, and three Indonesian language teachers. The model trial involved 10 students selected through random sampling. Data were collected through interviews, questionnaires, observations, and a speaking skills rubric, then analyzed to determine feasibility and improvement in students’ performance. The results indicated that the developed model was considered feasible by expert validators and practical for implementation in school counseling services. During the trial, students showed increased participation, confidence, interaction, and speaking performance. These findings suggest that integrating social constructivist principles into group counseling can provide an effective alternative service for enhancing students’ speaking skills in senior high schools.